Marketing analysis of the assortment of expectorant herbal medicines for the treatment of cough in arvi - Єренко, Олена Костянтинівна; Малюгіна, Олена Олександрівна; Бушуєва, Інна Володимирівна; Хортецька, Тая Володимирівна; Смойловська, Галина Павлівна; Khortetska, T. V.; Yerenko, O. K.; Maliuhina, O. O.; Bushueva, I. V.; Smoylovska, G. P. (My University, 2024)
Of particular concern to family doctors and healthcare professionals is the rather high incidence of acute respiratory viral infections accompanied by cough.
Keywords: market analysis; pharmaceutical market of Ukraine; respiratory system; cough; expectorants; herbal remedies